Regression test framework based on extended system dependence graph for object-oriented programs - Musa, Samaila; Md Sultan, Abu Bakar; Abd Ghani, Azim; Bahrom, Salmi (2014)
This paper presents a regression testing framework for object-oriented software based on extended system dependence graph model of the affected program. The approach is based on semantic analysis of the code. The goal is to identify changes in a method’s body due to data dependence, control dependence and dependent due to object relation such as inheritance and polymorphism. To find the affected statements due to changes in the program, we used affected statement as slicing criterion to performed slicing on the constructed graph. The methods affected are determined by analysis of the ESDG based on the affected statements. Test cases that execute the affected methods are selected from an existing test suite. New test cases are generated when necessary. The selected test cases are prioritized by assigning weight to the affected methods. A case study will be reported to provide evidence of the feasibility of the approach and its benefits in increasing the rate of fault detection and reduction in regression testing effort.